O PREGADOR SILENCIOSO: Ecumenismo no jornal Expositor Cristão (1886-1982) - Tunes, Suzel Magalhães (2009)
The Expositor Cristão, which is the official newspaper of the Methodist Church in Brazil, started in 1886, with what could be called an ecumenic proposition: it´s first name, Methodista Catholico (Catholic Methodist), uncovers the desire for universalism, as shown in the first number editorial. It´s creator, a north american missionary called John James Ransom intended a non sectarian doctrinarian and orientational newspaper, in accordance with the wesleyan tradition. But the Methodista Catholico had a short life: within less than a year it became the Expositor Cristão. The brazilian religious field was then under an apologetic controversy, with the insertion of mission protestantism, from anglo-saxon origin, opposing the Roman Catholicism. The name of the newborn newspaper was one more victim of the confrontations. This work put itself to evaluate how the newspaper treated the question of ecumenism since this period until the entry of the Methodist Church in the CONIC, National Council of Christian Churches, at the beginning of the decade of 1980. The research found that the deep rooted anti catholicism in brazilian Methodism at it´s prime never disappeared completely. Also realised that the Methodism was not immune to the conflicts that existed among the denominations of the evangelical world. In spite of the well acknowledged pioneering of the Methodist church in creating brazilian ecumenic organisations, ecumenism always faced internal barriers, more or less disguised. The newspaper Expositor Cristão, created to be a medium of information and doctrinarian formation, not always showed with the necessary clarity which meaning the Methodist Church confer to the word ecumenism and how the Church practices it. In some moments, the coexistence between ecumenism and anti ecumenism in the heart of the methodist field was not brought under the light of the debates of the newspaper, but remained hidden due to omissions and ambivalences. This is what this work could notice from a qualitative evaluation of the newspaper content´s.(AU)